Dosimetric effect of uncorrected rotations in lung SBRT with stereotactic imaging guidance. (October 2017) - Liu, Han; Andrews, Martin; Markovich, Andrey; Zhuang, Tingliang
Highlights: Logistic regression was used to quantify effect of uncorrected rotation with Exactrac guidance. Two types of rotations, around the treatment isocenter or a setup isocenter, were investigated. Clinical guidance on when rotations could be ignored based on treatment geometry was provided. Abstract: Purpose: To evaluate the dosimetric impact of uncorrected rotations on the planning target volume (PTV) coverage for early stage non-small cell lung cancer patients treated with stereotactic body radiotherapy using Brainlab ExacTrac image guidance. Methods: Twenty-two patients were retrospectively selected. Two scenarios of uncorrected rotations were simulated with magnitude of 1°, 2°, 3° and 5°: (1) rotation around the treatment isocenter; and (2) roll and yaw rotations around a setup isocenter. The D 95 of PTV from recalculated dose on the rotated CT was compared to that from the clinical plan. A logistic regression model was used to predict the probability of dose differences between recalculated and original plans that are less than 2% based on the rotation angle, PTV volume, and distance between the treatment and setup isocenter. Results: Logistic regression model showed the uncorrected isocentric rotations of up to 2.5° in all directions have negligible dosimetric impact. For non-isocentric rotations, a rotational error of 2° may cause significant under-dose of the PTV. Statistically significant ( p < 0.05) parameters in the logistic regression model were angle for isocentric rotations, angle and distance for non-isocentric roll rotations, and angle, distance and the PTV volume for non-isocentric yaw rotations. Conclusions: The severity of the dose deviations due to uncorrected rotations depends on the type and magnitude of the rotation, the volume of the PTV, and the distance between the treatment and setup isocenter, which should be taken into consideration when making clinical judgment of whether the rotational error could be ignored.